A Study on the Development of Data Literacy Content Framework for Elementary School Students - Moon, Hyunwoo; Go, HakNeung; Kim, Seong-Won; Lee, Youngjun (Society of Visual Informatics, 2025)
This study aimed to develop a data literacy content framework for elementary school students to establish a foundation for systematic data literacy education. The research was conducted through a literature review and analysis of the 2022 Revised National Curriculum of Korea. Based on Ridsdale et al. (2015)'s framework, components of data literacy suitable for elementary students were derived, and curriculum achievement standards related to data literacy were analyzed to develop the content framework. The research identified eight key components of data literacy: understanding data, data collection, data evaluation, data organization, data analysis, data visualization, data-driven decision-making, and data ethics. Curriculum analysis revealed that science (36.3%) and social studies (32.7%) subjects contained the highest proportion of data literacy elements, with grades 5-6 (63.2%) including more achievement standards than grades 3-4 (36.8%). The developed framework is categorized into three domains: knowledge and understanding, processes and skills, and values and attitudes. It considers grade-level hierarchy by focusing on basic concepts and simple functions for grades 3-4, while emphasizing complex concepts and higher-order functions for grades 5-6. This study contributes to supporting systematic data literacy education in elementary schools by providing a content framework that considers students' cognitive developmental stages and is expected to foster future core competencies through practice-centered education. Further research is needed to verify practical applicability, develop teaching and learning methods, and strengthen connections between school levels.